PENGARUH KEPERCAYAAN MEREK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN PADA RESTORAN SEDERHANA DI HARBOUT BAY BATAM - Agung Edy Wibowo; Agung Arif Gunawan (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2022)
This research aims to know and analyze the influence of brand trust and promotion towards customer buying decision at Sederhana’s Restaurant at Harbour Bay Batam. Brand trust is a set of thinking or other perception measurement to be commuted for obtaining confidence level of acceptance product or services.. Promotion is communication for assuring potential consumer about services and goods. Buying decision is a final action after selecting and concluding what next to do based on the information gathered. Sample were taken using purposive sampling method, and data collecting technique using survey method, through questionnaire. Sample size was taken t100 respondent, and final analysis were used multiple regression. This research aims to obtain outcome on the analysis of brand trust and promotion to consumer buying decision. The result of this study or test shown or conclude that brand trust has significant influence to the buying decision. It meant first hypotheses in this research was proved, or accepted. Promotion has significant influence to the buying decision. It meant secondary hypotheses in this research was proved, or accepted. And the result for the simultaneous test of two variables shown influence to the buying decision.It meant,third hypotheses can be proved or accepted.